Do Clinical Standards for Diabetes Care Address Excess Risk for Hypoglycemia in Vulnerable Patients? A Systematic Review. (28th February 2013) - Berkowitz, Seth A.; Aragon, Katherine; Hines, Jonas; Seligman, Hilary; Lee, Sei; Sarkar, Urmimala
<x xml:space="preserve">Abstract</x> Objective To determine whether diabetes clinical standards consider increased hypoglycemia risk in vulnerable patients. Data Sources MEDLINE, the National Guidelines Clearinghouse, the National Quality Measures Clearinghouse, and supplemental sources. Study Design Systematic review of clinical standards (guidelines, quality metrics, or pay‐for‐performance programs) for glycemic control in adult diabetes patients. The primary outcome was discussion of increased risk for hypoglycemia in vulnerable populations. Data Collection/Extraction Methods Manuscripts identified were abstracted by two independent reviewers using prespecified inclusion/exclusion criteria and a standardized abstraction form. Principal Findings We screened 1, 166 titles, and reviewed 220 manuscripts in full text. Forty‐four guidelines, 17 quality metrics, and 8 pay‐for‐performance programs were included. Five (11 percent) guidelines and no quality metrics or pay‐for‐performance programs met the primary outcome. Conclusions Clinical standards do not substantively incorporate evidence about increased risk for hypoglycemia in vulnerable populations.